The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3892/ijo.2012.1735
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid significantly enhances radiation-induced apoptosis against human fibrosarcoma cells by inhibiting radioadaptive signaling

Abstract: Abstract. Zoledronic acid (ZOL), a third-generation bisphosphonate, inhibits bone resorption, as well as exhibiting direct antitumor activity. To date, however, the combined effects of ZOL and ionizing radiation (IR) have not been assessed in patients with soft tissue sarcoma. We have, therefore, assessed the combined effects of ZOL and IR in fibrosarcoma cells. HT1080 fibrosarcoma cells were treated with ZOL and/or IR, together or sequentially and the antitumor effects were assessed. We found that ZOL signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
5
11
0
Order By: Relevance
“…Production of ROS is an underlying mechanism of chemotherapy and radiotherapy [44]. Previous studies have shown that combined application of ZOL with panobinostat or ionizing radiation significantly enhanced apoptosis by elevating ROS levels [45], [46]. Here, we found that ZOL alone can induce apoptotic cell death and inhibit colony formation accompanied by an increase of ROS.…”
Section: Discussionsupporting
confidence: 54%
“…Production of ROS is an underlying mechanism of chemotherapy and radiotherapy [44]. Previous studies have shown that combined application of ZOL with panobinostat or ionizing radiation significantly enhanced apoptosis by elevating ROS levels [45], [46]. Here, we found that ZOL alone can induce apoptotic cell death and inhibit colony formation accompanied by an increase of ROS.…”
Section: Discussionsupporting
confidence: 54%
“…19, 40 A direct effect of ZOL as a single agent on ROS generation has not been shown before; however, a recent report demonstrated that the increased intracellular ROS levels and the cytotoxic effect induced by ionizing radiation in cancer cells are enhanced by cotreatment with ZOL and that this effect is reduced by NAC. 41 Notably, isoprenoids such as GGPP and FPP, which are inhibited in the cells treated with ZOL, are involved in the positive modulation of several nonsteroid isoprenoids (e.g., heme-A, coenzyme-Q10, and dolichols) that are related to antioxidant status. 42 In light of these data, we can hypothesize that ZOL treatment may potentiate HDACi-induced oxidative stress by inhibiting the biosynthesis of antioxidant isoprenoids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its bone-protective effects, ZA can prevent tumor progression (8). Due to its inhibition of the prenylation of small GTP-binding proteins, such as Ras, ZA inactivates Ras signaling and inhibits Ras-dependent cell proliferation (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%